Total Face Approach (TFA) 3D Cephalometry and Superimposition in Orthognathic Surgery: Evaluation of the Vertical Dimensions in a Consecutive Series - Perrotti, Giovanna; Baccaglione, Giulia; Clauser, Tommaso; Scaini, Riccardo; Grassi, Roberta; Testarelli, Luca; Reda, Rodolfo; Testori, Tiziano; Del Fabbro, Massimo (Methods and protocols, 2021)
Background: Cephalometry is fundamental in diagnosis, analysis, and planning of orthodontic-surgical treatment as it reveals skeletal relationship between the upper and lower jaw as well as facial aesthetic parameters. Nevertheless, 3D cephalometry has still not become the exam of choice in orthognathic treatment even though today CBCT (Cone Beam Computed Tomography) is routinely used in other branches of dentistry. Methods: In a sample of 13 patients undergoing bimaxillary orthognathic surgery a chin-vertex CBCT exam was prescribed prior to orthodontic treatment (OT) and 12 months after surgery (T1). The DICOM files uploaded to MaterialiseSimplant Ortho software pro 2.1 (Materialise Co., Leuven, Belgium) were analyzed following the multiplane 3D Total Face cephalometry protocol (TFA). Results: Results comparing pre-op and post-op TFA 3D cephalometry, were then evaluated considering reference values reported in literature. The CBCT, carried out pre- and post-surgery, were subsequently analyzed employing the superimposition method using cranial base as reference. The aim of this study is to evaluate the advantages and disadvantages of the two methods in orthognathic surgery. Conclusions: Multiplane 3D TFA allows the clinician to locate where major or minor skeletal discrepancies are found with respect to ideal parameters and is also useful in classifying skeletal intermaxillary relation. The superimposition method is highly intuitive but does not provide information on the quantity and location of osteotomic movement.